Why should clinical practitioners ask about their patients’ concerns about falling? - Ellmers, Toby; Freiberger, Ellen; Hauer, Klaus; Hogan, David B; McGarrigle, Lisa; Lim, Mae Ling; Todd, Chris; Martin, Finbarr; Delbaere, Kim (Age & ageing, 2023)
Concerns (or ‘fears’) about falling (CaF) are common in older adults. As part of the ‘World Falls Guidelines Working Group on Concerns about Falling’, we recommended that clinicians working in falls prevention services should regularly assess CaF. Here, we expand upon these recommendations and argue that CaF can be both ‘adaptive’ and ‘maladaptive’ with respect to falls risk. On the one hand, high CaF can lead to overly cautious or hypervigilant behaviours that increase the risk of falling, and may also cause undue activity restriction (‘maladaptive CaF’). But concerns can also encourage individuals to make appropriate modifications to their behaviour to maximise safety (‘adaptive CaF’). We discuss this paradox and argue that high CaF—irrespective of whether ‘adaptive’ or ‘maladaptive’—should be considered an indication that ‘something is not right’, and that is represents an opportunity for clinical engagement. We also highlight how CaF can be maladaptive in terms of inappropriately high confidence about one’s balance. We present different routes for clinical intervention based on the types of concerns disclosed.